Vendor Development Program Among Smis: A Malaysian Experience (Jurnal Kemanusiaan, 2017)
The supplier-buyer relationship has been increasingly undertaken in recent years, by academics, consultants and operations management. Present and especially future development strongly urge for more systematic and transparent decision-making. Developing longer-term relationships and using longer-term contracts, are additional ways to manage, develop and improve supplier performance (Monczka et al. 1998) who, often becomes a partner with the purchaser. This paper investigates the supplier development programme initiated by the government of Malaysia to stimulate the economic growth through SMIs sector in co-operation with the large firms (LFs). The economic and industrialisation development propelled by the government has encouraged the development of SMIs working closely with large firms (LFs). This programme was successfully implemented when the government introduced it in the heavy industrial program-the manufacturing of national car PROTON in 1988. The success story of PROTOB has initiated the government to disseminate this programme into other industries. Empirical findings from a survey of 15 SMIs and 6LFs (from 4 different industrial sectors) within the Klang Valley in the supplier development programme indicated that the success rate is not encouraging. Suppliers lack skills and financing to make the necessary investments in training, new technology, research and development to make an effective partnership with final producers.